Double-pass erbium-doped zirconia fiber amplifier for wide-band and flat-gain operations - Harun, Sulaiman Wadi; Paul, Mukul Chandra; Huri, N.A.D.; Hamzah, Azura; Das, Shyamsundar P.; Pal, Mrinmay; Bhadra, Shyamal Kumar; Ahmad, Harith; Yoo, Seong Woo; Kalita, Mridu P.; Boyland, Alexander J.; Sahu, Jayanta Kumar S. (Elsevier, 2011)
The double-pass erbium-doped zirconia fiber amplifier (EDZFA) is proposed and demonstrated to provide a wide-band amplification as well as flat-gain operation in both the C- and L-band regions using only a single-gain medium. The proposed amplifier utilizes an erbium-doped zirconia fiber (EDZF) with erbium ion concentration of 2800 ppm as a gain medium. The medium is fabricated in a ternary glass host, zirconiayttriaaluminum codoped silica fiber through solution doping technique along with modified chemical vapor deposition (MCVD). Compared to a single-pass operation, the double-pass EDZFA shows a better gain performance. At input signal power of 0 dBm and the optimum EDZF length of 2 m, a flat gain of around 16 dB is achieved by the proposed double-pass amplifier with gain variation of approximately 2.5 dB throughout the wavelength range from 1530 to 1590 nm. However, the noise figure of the double-pass amplifier is slightly higher than that of the single-pass due to inefficient population inversion at the input part of the amplifier.